2021
DOI: 10.1186/s12909-021-02504-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the pediatric life support instructors courses

Abstract: Objective To evaluate the results and quality of pediatric cardiopulmonary resuscitation (CPR) instructor training courses. Methods A retrospective analysis was performed of the results of 24 pediatric CPR instructor courses held over 21 years (1999 to 2019). The results of participants’ evaluation of theory and practice sessions were analyzed. In addition, participants were asked to answer an anonymous survey to assess their opinion on the quality… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A search of the databases identified a total of 13 219 records. After removing 2909 duplicates, 10 310 records were screened by reviewing the titles and abstracts; 107 potentially relevant records were included in the full‐text assessment and a total of 20 studies, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 including 5 conference abstracts, 15 , 21 , 25 , 26 , 31 1 short communication 29 and 14 full‐length articles, † were included in the final analysis. A flow diagram of the reviewing process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A search of the databases identified a total of 13 219 records. After removing 2909 duplicates, 10 310 records were screened by reviewing the titles and abstracts; 107 potentially relevant records were included in the full‐text assessment and a total of 20 studies, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 including 5 conference abstracts, 15 , 21 , 25 , 26 , 31 1 short communication 29 and 14 full‐length articles, † were included in the final analysis. A flow diagram of the reviewing process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…A flow diagram of the reviewing process is shown in Figure . There were 6 randomized controlled trials, 12 , 14 , 16 , 17 , 18 , 20 12 nonrandomized studies, 15 , 19 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 and 2 descriptive surveys. 13 , 23 Interventions in the included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pediatrics residents are graduating with poor self-perceived competency in emergency skills such as bag-mask ventilation and foreign body removal [ 5 ]. Whereas pediatricians may have difficulty dealing with arrhythmias, CPR and trauma, junior nurses face the thorny issue of how to perform neonatal CPR, possibly due to a lack of relevant clinical experience [ 6 , 7 ]. The low level of first aid knowledge among pediatric health care providers explains the rise of emergency literacy training.…”
Section: Introductionmentioning
confidence: 99%